Atributos da qualidade: um estudo exploratório em serviços de estética e beleza - Bota, Fátima Barbosa (2007)
The main purpose of this exploratory work is to investigate the attributes that motivate customers to choose services within beauty and aesthetic centers. Everyday, we are taking by surprise due to the discovery of new procedures that will make many dreams come true regarding youth¿s prolong. Customers are much more demanding now, so the beauty industry must emphasize the importance of beauty in our day lives. The old age fears, the need of men and women in getting close to the perfect beauty and looking great explaining the reason many customer looking for beauty and aesthetic centers to ¿postpone¿ the inevitable old age.This work focus on the increase of beauty and aesthetic industry market position, the quality of service provide by these centers, emphasize the concepts of service quoted by different authors, for instance, Lovelock (2006), Las Casas (2002), Kotler (1998), the characteristics of services, the behaviour of customers, the conceptualized models of service quality from Albrecht and Zemke (1998), moments of truth according to Carlzon (1994).This work presents a summary of beauty along the years; shows the methodology used and the interviews results showing the main quality service attributes in beauty and aesthetic centers; the difficulty faced and suggestion for future research.